Effects of forearm compression sleeves on muscle hemodynamics and muscular strength and endurance parameters in sports climbing: A randomized, controlled crossover trial - Limmer, M.; de Marées, M.; Roth, R. (Frontiers in Physiology, 2022)
Purpose: Wearing compression garments is a commonly used intervention in sports to improve performance and facilitate recovery. Some evidence supports the use of forearm compression to improve muscle tissue oxygenation and enhance sports climbing performance. However, evidence is lacking for an effect of compression garments on hand grip strength and specific sports climbing performance. The purpose of this study was to evaluate the immediate effects of forearm compression sleeves on muscular strength and endurance of finger flexor muscles in sports climbers.